The Implementation Of The Discovery Learning Model In Early Childhood Thematic Learning To Enhance Children’s Imagination At Tk Pertiwi 2 Deroduwur, Wonosobo - Wajriati Wajriati; Ahmad Khoiri; Vava Imam Agus Faisal (FKIP UNSULTRA, 2026)
This study was motivated by the low imaginative ability of Group B children at TK Pertiwi 2 Deroduwur Wonosobo, which was reflected in passive behavior, lack of confidence, and a tendency to imitate their peers’ work during learning activities. The research aimed to examine the effectiveness of the Discovery Learning model in improving children’s imagination through thematic learning activities based on exploration. The study employed a quantitative experimental approach using a One Group Pretest-Posttest Design involving 15 kindergarten children. Data were collected through observation, documentation, and pretest-posttest assessments measuring fluency, flexibility, originality, and elaboration aspects of imagination. The findings revealed a significant improvement in children’s imaginative abilities after the implementation of discovery-based learning. The average score increased from 1.85 in the pretest to 3.33 in the posttest. Furthermore, the N-Gain result reached 0.702, categorized as high or effective. Therefore, the Discovery Learning model was proven effective in enhancing early childhood imagination and creativity through environmental exploration activities. These results indicate that discovery-based thematic learning not only improves quantitative achievement scores but also supports the development of creative thinking skills in early childhood education.